2018
DOI: 10.1073/pnas.1710670115
|View full text |Cite
|
Sign up to set email alerts
|

Rogue waves and large deviations in deep sea

Abstract: The appearance of rogue waves in deep sea is investigated by using the modified nonlinear Schrödinger (MNLS) equation in one spatial dimension with random initial conditions that are assumed to be normally distributed, with a spectrum approximating realistic conditions of a unidirectional sea state. It is shown that one can use the incomplete information contained in this spectrum as prior and supplement this information with the MNLS dynamics to reliably estimate the probability distribution of the sea surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
101
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 47 publications
3
101
0
Order By: Relevance
“…A burgeoning field of research explicitly links rare event simulation and analysis tools with geophysical applications [9][10][11][12][13][14] . In a recent paper, Ragone, Wouters and Bouchet 12 showed that rare event sampling methods can be used to study the probability of extreme weather occurring.…”
Section: Introductionmentioning
confidence: 99%
“…A burgeoning field of research explicitly links rare event simulation and analysis tools with geophysical applications [9][10][11][12][13][14] . In a recent paper, Ragone, Wouters and Bouchet 12 showed that rare event sampling methods can be used to study the probability of extreme weather occurring.…”
Section: Introductionmentioning
confidence: 99%
“…A statistical approach to this problem has important limitations, such as requiring various extrapolation schemes due to insufficient sample numbers (see extreme value theorems [18]). Another strategy is large deviations theory [24,7], a method for the probabilistic quantification of large fluctuations in systems, which involves identifying a large deviations principle that explains the least unlikely rare event. While applied to many problems, for complex systems estimating the rate function can be very costly and the principle does not characterize the full probability distribution.…”
Section: Introductionmentioning
confidence: 99%
“…These extreme events produce values of the observable that are several standard deviations away from its mean, resulting in heavy tails of the corresponding probability distribution. Important examples include climate phenomena (1,2), rogue waves in oceanic and optical systems (3,4,5) and large deviations in turbulent flows (6,7,8). Since such extreme phenomena typically have dramatic consequences, their quantification and prediction is of great interest.…”
Section: Introductionmentioning
confidence: 99%